Produção de plantas de espécies lenhosas ribeirinhas por via seminal: técnicas e resultados - Fabião, António (2009)
Rehabilitation of woody riparian galleries largely depends on the availability of seedlings or seeds of autochthonous species, which are usually difficult to obtain in Portugal. The cultural value of autochthonous seeds of several riparian woody species in nursery conditions was evaluated in order to assess seedling production feasibility. The choice of species was based on their occurrence in riparian habitats, even if not exclusive to such environments, and their suitability to establishment studies currently under way. The results indicate that seeds of Celtis australis, Fraxinus angustifolia, Quercus robur, Q. faginea and Platanus × hybrida obtained in Portugal were highly suited to seedling production. Germination of seeds of Acer pseudoplatanus and A. campestre was much more irregular and seeds from Alnus glutinosaand Crataegus monogyna exhibited a very low germination rate. We conclude that seedling production of European hackberry, oaks, narrow-leaved ash, and plane tree and, less clearly, maples, can be successfully carried out in nursery conditions using simple and unsophisticated sowing techniques. For common alder and whitethorn it is preferable to produce seedlings via vegetative propagation as an alternative to more sophisticated nursery pre-germination treatments.